Against the Grain: What Motivates Entrepreneurs to Locate in Pennsylvania's Non-Metropolitan Cities and Boroughs - Michael Fortunato; Theodore Alter (European Regional Science Association (ERSA), 2010)
Pennsylvania is a state whose rural cities and towns - once prosperous centers of manufacturing and agricultural production - have seen steady economic declines in these sectors due to macro-economic restructuring. Global economic forces have resulted in the loss or downgrade of many local jobs, population declines, the loss of educated youth to growing metropolitan areas, and the abandonment of small businesses from many small downtowns. Despite these trends, most small towns and cities still retain a substantial core of new business activity. These entrepreneurs hold the promise of reviving the lagging local economy by providing new jobs and critical products and services that are targeted to local tastes and needs. Understanding what led them to start a business in a declining area can lead to the development of new strategies to entice more entrepreneurs to locate a business in the area to stimulate local economic development. This report uses interviews with forty-two entrepreneurs in eight small towns across Pennsylvania to understand what specific factors motivated their decision to locate in areas traditionally marked by economic decline. The report reveals the surprising fact that most small town entrepreneurs are not natives, but were attracted to the area for other reasons. The report also explores which factors were more important to the location decision - personal, individualist factors or factors within the local social and physical environment. A conceptual framework of the location decision in Pennsylvania is developed, and real strategies for bolstering local entrepreneurship, especially in areas formerly engaged in manufacturing, are drawn from the findings.
Keywords: 330